2013
DOI: 10.2308/iace-50448
|View full text |Cite
|
Sign up to set email alerts
|

The Marketability of Options for Meeting the 150-Hour Requirement: An Empirical Analysis of Public Accounting Firm Recruiting Intentions

Abstract: Students are often concerned with, and advisors are often confronted with, questions about the best way to obtain the 150 hours required for CPA licensure in most states and jurisdictions. This research provides insight through an experiment in which CPAs in public accounting provide assessments about how actively their organization would recruit job candidates whose profile descriptions differ only as to how they met the 150-hour requirement. By manipulating, at seven levels, the independent variable describi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Metrejean, Metrejean, & Stocks (2008) found no difference in how actively students were recruited based on the level of degree completed. Mauldin, Braun, Viosca, Jr., & Chiasson (2013) found that students who had completed a master's degree enhanced their chances of being recruited for employment. For students that did not have an opportunity for a master's degree, they found that a double major in information systems or finance provided a competitive edge.…”
Section: Completing 150-hoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Metrejean, Metrejean, & Stocks (2008) found no difference in how actively students were recruited based on the level of degree completed. Mauldin, Braun, Viosca, Jr., & Chiasson (2013) found that students who had completed a master's degree enhanced their chances of being recruited for employment. For students that did not have an opportunity for a master's degree, they found that a double major in information systems or finance provided a competitive edge.…”
Section: Completing 150-hoursmentioning
confidence: 99%
“…In fulfilling the 150-hour requirement Bierstaker, Howe, & Seol (2004) found that students at public universities preferred taking additional accounting credits, while students at private colleges preferred taking more non-accounting business credits. Mauldin, Braun, Viosca, Jr., & Chiasson (2013) found that CPAs prefer additional credits in accounting to meet the 150-rule, preferably in graduate credits.…”
Section: Completing 150-hoursmentioning
confidence: 99%
“…Meanwhile, Master of Business Administration (MBA) graduates had higher prospects for promotion from manager to partner, typically the most coveted level for those wanting careers in public accounting. While there have been favorable considerations for pursuing graduate education in accounting, especially if an individual is pursuing the CPA, other factors such as wanting more leadership and soft skill training may lead students to pursue other programs such as the MBAMauldin et al, 2013). On the other hand, graduates may choose to gain another technical skillset my pursuing other specialized graduate degrees from in-demand areas such as cybersecurity.…”
mentioning
confidence: 99%